Substitusi Tepung Kacang Koro Pedang (Canavalia ensiformis (L.) DC.) pada Pie Susu Ditinjau dari Sifat Organoleptik, Kandungan Gizi dan Unit Cost - Clariza Arwi Nursalma; Setyowati Setyowati; Almira Sitasari (Pusat Unggulan Iptek (PUI) Poltekkes Kemenkes Yogyakarta, 2021)
An effort to reduce dependence on wheat flour is to use wheat flour made from local commodities. Koro bean flour can be used in making milk pies because it has a high nutritional content so that it can support community nutrition, and has a high economic value. The research method used is pure experiment. Organoleptic test data were analyzed using the K-Independent sample test (Kruskall-Wallis). If there is a difference, continue with Mann Whitney. The nutritional content data were analyzed using the Anova test while the Unit Cost data were analyzed descriptively. The results of the organoleptic test showed that there was a significant difference in the level of preference for the color, aroma, taste, and texture of the milk pie with the substitution of Jack bean flour. The results of the nutritional content test showed that the higher the substitution of koro bean flour, the higher the protein content. The result of unit cost analysis shows that the more substitutions of Jack bean flour, the higher the unit cost. The substitution of Jack Bean flour affects the organoleptic properties (color, aroma, taste, and texture), protein content of milk pie, and unit cost of milk pie. However, it has no effect on the energy, fat, and carbohydrate content of milk pie.